The effect of complementary music intervention on the patients’ quality of life after septoplasty and rhinoplasty - Schell, Angela; Waßmer, Felix; Zaubitzer, Lena; Kramer, Benedikt; Sadick, Haneen; Rotter, Nicole; Häussler, Daniel (BMC complementary medicine and therapies, 2022)
Quality of life (QoL) assessment has emerged as an important evaluation tool for therapeutic treatments. The positive impact of complementary music interventions on QoL has been demonstrated in the literature, particularly in chronic and malignant diseases. However, its benefits during the perioperative period in head and neck patients have not been investigated thus far. Head and neck patients undergoing septoplasty and rhinoplasty were prospectively randomized and consecutively included in the trial. Passive music intervention (60 min per day) was applied to the intervention group. QoL was assessed using the Nasal Obstruction Symptom Evaluation (NOSE) questionnaire and the Functional Rhinoplasty Outcome Inventory 17 (FROI-17) questionnaire at three visits during the postoperative phase. Pain was measured using a visual analogue scale. Forty-four patients were enrolled in the study. The NOSE score between the control group and the intervention group in the septoplasty arm differed significantly at visit #2 (p < 0.001) and visit #3 (p < 0.015). For the rhinoplasty study arm, significant differences in the FROI-17 score were also found at visit #2 and visit #3 (p = 0.04). Complementary music interventions can considerably improve patients’ QoL during the postoperative period. Furthermore, passive music interventions may be easily implemented in clinical practice as an additional cost-effective treatment with ubiquitous availability.
Gesehen am 24.07.2023